Theoretical basis of the first-year student’s adaptation for the education conditions in the engineering pedagogical academy - Paiunova, A. (Problems of Engineer-Pedagogical Education, 2018)
The study devoted to the actual topic «Theoretical basis of the first-year students adaptation to the education conditions in the engineering and pedagogical academy». The specificity of engineering and pedagogical education was considered. Three main adaptation aspects of the firstyear student education in the engineering and pedagogical academy were determined in the article. The author has done a research among first-year student’s in the educational scientific professional and pedagogical institute Ukrainian Engineering and Pedagogical Academy (Bakhmut). The results of pilot study were showed that said about the difficulties of the first-year students’ adaptation. The systems of psychological and educational actions for adaptations accelerate of the first-year students were determined. Accelerate ways of the first-year students adaptation for the education system in the engineering and pedagogical academy were suggested in the article. The author pays special attention to the Internet project as the adaptation way of the first-year students to the educational system in the engineering and pedagogical academy.